ML-13 AN ATTEMPT OF RECHALLENGE OF HD-MTX AND MAINTENANCE THERAPY OF MTX FOR PATIENTS WITH PCNSL - Yamaguchi, Takashi (Neurooncol Adv, 2019)
PURPOSE: High dose methotrexate (HD-MTX) followed by radiotherapy (RT) is a standard therapy for primary CNS malignant lymphoma. However, the delayed neuronal toxicity due to RT is a serious problem especially for elderly patients. To avoid RT toxicity, we performed re-challenge of HD-MTX until complete remission (CR). Furthermore, we started maintenance therapy (MT) with MTX for elderly and poor Karnofsky Performance Scale (KPS) patients and reported the interim results. METHODS: We performed HD-MTX (3.5g/m(2)) therapy until achieving CR for patients whose ages were older than 70 years old and KPS were less than or equal to 60%. After having CR, 3 courses of MT of MTX (3g/patient) for 3 weeks were introduced every 3–4 months for 2 years. In cases of recurrence, HD-MTX was repeated. But when CR was not achieved by HD-MTX, RT was introduced. RESULTS: Number of patients was 8. Median age, median KPS, and median follow up periods were 73.5y.o. (71–78), 40% (30–60), and 4.5mo. (1–42), respectively. CR rate was 75% but two patients did not achieve CR. One patient had a complication of acute tubular necrosis just after first use of HD-MTX and another died due to pneumocystis pneumonia after 4(th) HD-MTX. Two patients without RT maintained CR and good KPS over 2 years. Four patients with RT maintained CR but their KPS gradually deteriorated. DISCUSSION: Rechallenge of HD-MTX exhibits better results and comparable safety with standard treatment, but RT was unavoidable. In order to avoid RT, we started MTX maintenance therapy for elderly and poor KPS patients before recurrence. Our maintenance therapy is easy and good disease control for patients who had not received RT, however there were two serious adverse events. CONCLUSION: Rechallenge of HD-MTX and maintenance therapy of MTX might be promising but dangerous for elderly patients. Further careful assessment is needed.